Patient and hospital factors associated with induction mortality in acute lymphoblastic leukemia. Issue 5 (19th November 2013) - Seif, Alix E.; Fisher, Brian T.; Li, Yimei; Torp, Kari; Rheam, Douglas P.; Huang, Yuan‐Shung V.; Harris, Tracey; Shah, Ami; Hall, Matthew; Fieldston, Evan S.; Kavcic, Marko; Vujkovic, Marijana; et al.
<x xml:space="preserve">Abstract</x> Background Deaths during induction chemotherapy for pediatric acute lymphoblastic leukemia (ALL) account for one‐tenth of ALL‐associated mortality and half of ALL treatment‐related mortality. We sought to ascertain patient‐ and hospital‐level factors associated with induction mortality. Procedure We performed a retrospective cohort analysis of 8, 516 children ages 0 to <19 years with newly diagnosed ALL admitted to freestanding US children's hospitals from 1999 to 2009 using the Pediatric Health Information System database. Induction mortality risk was modeled accounting for demographics, intensive care unit‐level interventions, and socioeconomic status (SES) using Cox regression. The association of ALL induction mortality with hospital‐level factors including volume, hospital‐wide mortality and payer mix was analyzed with multiple linear regression. Results ALL induction mortality was 1.12%. Race and patient‐level SES factors were not associated with induction mortality. Patients receiving both mechanical ventilation and vasoactive infusions experienced nearly 50% mortality (hazard ratio 122.30, 95% CI 66.56–224.80). Institutions in the highest induction mortality quartile contributed 27% of all patients but nearly half of all deaths (47 of 95). Hospital payer mix was associated with ALL induction mortality after adjustment for other hospital‐level factors (P = 0.046). Conclusions The overall risk of induction death is low but substantially increased in patients with cardio‐respiratory and other organ failures. Induction mortality varies up to three‐fold across hospitals and is correlated with hospital payer mix. Further work is needed to improve induction outcomes in hospitals with higher mortality. These data suggest an induction mortality rate of less than 1% may be an attainable national benchmark. Pediatr Blood Cancer 2014;61:846–852. © 2013 Wiley Periodicals, Inc.